Analisis Flyrock Handling Dalam Kegiatan Peledakan Untuk Mendapatkan Radius Aman Alat Pada Quarry Bukit Karang Putih PT. Semen Padang Sumatera Barat - Jeffry - Albadri; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2022)
PT. Semen Padang is a mining company that uses the open pit mining method, namely Quarry Side Hill mining, which is mining method carried out to excavate deposits of industrial minerals or non-mettalic minerals. The rock to be transported to the crusher must be blasted first. The quality of the blasting results will determine the success of the blasting activity. Explosives release a large amount of energy during an explosion, only 20-30% is used to crush and move rocks and the rest is wasted in the form of environmental side effects. One of the impacts of blasting activities on the environment in the area around mining is a flyrock. At 15:15 location PT. Semen Padang, precisely on front 5, is located close to one of the generator units which is also a spotlight, this unit is 63 m from the blasting location. The author finds several flyrock throwing directions that are not in accordance with the freeface direction, but sideways or in an unwanted direction and produce excess flyrock that can hit the generator unit or equipment behind or beside the blasting area which was thought to be safe before. Flyrock throwing distance analysis will be carried out using the RIchard & Moore empirical model and Ebrahim Ghasemi dimensional analysis model.